From adventures to diagnosis: adolescent behavior in classic fiction through the eyes of newly licensed Czech psychiatrists – a vignette study - Pisl, Vojtech; Hodkova, Andrea; Hudecek, Jiri; Pav, Marek; Vevera, Jan (Frontiers in Psychiatry, 2025)
IntroductionYouth mental health is a growing concern, with reports of psychiatric diagnoses becoming increasingly prevalent. Among other factors, psychiatrization may inflate the observed prevalence by interpreting experiences previously understood as adversities inherent to human life as symptoms of psychopathology. The current study explores the pathologization of behaviors typical of adolescence by asking contemporary psychiatrists to diagnose and treat a character from a novel who is considered a prototypical teenager of the 19th century: Tom Sawyer.MethodsA one-page vignette was distributed either in sealed envelopes or via email to 57 psychiatrists who had obtained their license for independent practice between 2021 and 2023 in the Czech Republic. In total, 47 psychiatrists took part, yielding an overall response rate of 82%. The number and frequency of diagnostic conclusions, prescribed medications, and recommended interventions are reported.ResultsMost respondents diagnosed the boy described in the vignette with a psychiatric disorder (94%; CI = 81–98%) and recommended an intervention within the healthcare system (89%; CI =76–96%). Two thirds (62%, CI = 46–75%) recommended pharmacotherapy: antidepressants (27%), antipsychotics (22%), stimulants (13%), and anxiolytics (2%); 68% (53–80%) recommended psychotherapy. Nonmedical interventions (e.g., counseling, social services) were recommended by 49%.ConclusionsThe experiences of an adolescent boy, once interpreted as normative “adventures” in the 19th century, were recognized by newly certified psychiatrists as psychiatric disorder. These findings illustrate the extent of psychiatrization over time and suggest that expert diagnoses may substantially contribute to the overinterpretation of problems of living as psychiatric disorders.